PERLINDUNGAN HUKUM TERHADAP ANAK PELAKU TINDAK PIDANA YANG MELAKUKAN PENYALAHGUNAAN NARKOBA - Anisa Puspita Sari Wijaya; I Gusti Ngurah Nyoman Krisnadi Yudiantara (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The purpose of this study is to discuss how to apply legal protection to child drug abusers and how legal policies are applied to child perpetrators. This study uses a normative legal research type and data collection through literature and reviewing existing laws. The results of the study indicate that if a child is proven to have committed drug abuse, the criminal procedure that applies to him is diversion, or a special criminal process for children, because its nature is different from general criminalization; with procedural steps like this, it certainly makes the Indonesian state proven to always prioritize the interests of children by not equating their criminal rights with adults.